Survey of Supplement Use and Effects Felt by Amateur Boxers (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. To investigate type of supplement and amount of supplement used as well as the perceived effect and needs of boxers. Materials and methods. This research is a survey conducted from December 2022 to January 2023. The instrument used a questionnaire (google form).Boxers have 2 criteria, namely: 1) are still active as athletes and 2) have been champions at the provincial level with a total of 155 boxers, 116 male boxers and 39 female boxers. Results. 74 boxers used more than 1 type of supplement (48%), 81 boxers used only 1 type of supplement (52%). Type of supplement, Creatine 23 boxers (8.1%). Whey Protein 14 boxers (4.9%), Fat Burner 93 boxers (32.9%). BCAA 26 boxers (9.2%). Amino 12 boxers (4.2%). Multivitamins and minerals 114 boxers (40.7%). The effect felt, 22 boxers felt effect is "very low" (14.21%), 40 boxers felt effect is “low” (25.80%), 53 boxers felt effect is "enough" (34.19%), 14 boxers felt effect is “high” (9.03%), 26 boxers felt effect is “very high” (16.77%). The need to use supplements, namely 7 boxers need supplements is "very low" (4.54%), 13 boxers need supplements is “low” (8.38%). 52 boxers need supplements is “enough” (33.54%). 44 boxers need supplements is "high" (28.38%). 39 boxers need supplements is "very high" (25.16%). Conclusion. Multivitamins and minerals and fat burners are popular supplements used by boxers because of their convenience and more beneficial benefits. However, boxers are still less concerned about how to use supplements. It is evident from the results that show that many boxers feel in the categories of "enough", "low" and "very low" in the use of supplements but boxers think that the use of supplements is really needed. Further research is expected, to determine the amount and type of supplement recommended specifically for boxing athletes.